Unrepaired Complete Tracheal Rings: Natural History and Management Considerations. (April 2018) - Wilcox, Lyndy J.; Hart, Catherine K.; de Alarcon, Alessandro; Schweiger, Claudia; Peddireddy, Nithin S.; Tabangin, Meredith; Rutter, Michael J.
Objectives: To document the natural growth pattern of unrepaired complete tracheal rings (UCTRs) and describe the patient population managed conservatively. Study Design: Case series with chart review. Setting: Tertiary pediatric academic center. Subjects/Methods: Medical records of patients with confirmed complete tracheal rings on bronchoscopy from 1993 to 2017 were reviewed. Patients aged 0 to 18 who had documented tracheal sizing over time and did not require surgical intervention were included. Exclusion criteria included tracheal stenosis not caused by complete tracheal rings. Comorbidities and airway characteristics were documented in addition to endoscopic findings. These were compared with children requiring surgical repair. Results: In total, 149 patients with complete tracheal rings were identified. Twenty-five had UCTRs for an overall 16.8% rate of conservative management. Nineteen patients met inclusion criteria and underwent a total of 90 microlaryngoscopy and bronchoscopies (MLBs) with sizing. The growth of the UCTRs over time, based on MLB sizing, was chronicled. The median airway growth noted was 0.38 mm/y. A moderately strong positive correlation was seen between age and airway size ( rs = 0.72, P < .0001). Children with UCTRs were less likely to have long-segment involvement than those who required repair (92%, P = .024). Conclusions: A select group of children with complete tracheal rings can be managed expectantly without surgical intervention. Conservative management may be less successful in children with long-segment complete tracheal rings. Airway growth does occur in this population and can be monitored over time. Having a standardized method for sizing UCTRs allows for more effective communication between providers and assurance of continued growth of the airway while following these patients.